Pengaruh Efikasi Diri Dan Disposisi Matematis Terhadap Kemampuan Komunikasi Matematis Siswa Kelas X Smk - Wulan, Dewi; Meifiani, Nely Indra (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
The study aims to determine the effect of self-efficacy and mathematical disposition on students' mathematical communication skills at SMK N 2 Pacitan. Self-efficacy and mathematical disposition as independent variables. While the dependent variable is mathematical communication ability. The data collection instruments consisted of questionnaires and tests. The study used a quantitative approach with ex-post facto method, with a population of all class X students of SMK N 2 Pacitan totalling 480 students. Data analysis used the 3S-AR application. The regression analysis results showed that self-efficacy has a significant influence on mathematical communication ability with a correlation coefficient of 0.31 and a coefficient of determination of 9.8%. In contrast, mathematical disposition also had a significant but smaller effect, with a correlation coefficient of 0.26 and a coefficient of determination of 6.6%. When both variables were tested together, only self-efficacy showed a significant effect, while mathematical disposition was not significant. This study confirms the importance of self-efficacy in improving students' mathematical communication ability, although mathematical disposition also contributes in a limited way.